Analyzing reading preferences based on gender and education with decision tree method - Sari, Jelita Permata; Ningsih, Maylinna Rahayu (Journal of Student Research Exploration, 2025)
This study aims to analyze the suitability of book genre selection with gender and education level. A classification method using a decision tree algorithm with four different criterion parameters is used to examine reading preferences based on various demographic factors, namely Gain Index, Information Gain, Gini Index, and accuracy. Data was obtained from a dummy dataset involving 120 records with three main attributes. The results show variations in accuracy depending on the criteria selected, with the highest accuracy rate achieved being 78.57%.